2004
DOI: 10.1113/jphysiol.2003.055889
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the excitability of cholinergic basal forebrain neurones by KATP channels

Abstract: The expression of ATP-sensitive K + (K ATP ) channels by magnocellular cholinergic basal forebrain (BF) neurones was investigated in thin brain slice and dissociated cell culture preparations using a combination of whole-cell, perforated-patch and single-channel recording techniques. Greater than 95% of BF neurones expressed functional K ATP channels whose activation resulted in membrane hyperpolarization and a profound fall in excitability. The whole-cell K ATP conductance was 14.0 ± 1.5 nS and had a reversal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…Thus, in previous experiments using these neurons in long-term culture, they showed the same electrophysiological properties as those reported for identified cholinergic BF neurons in situ (Allen and Brown, 1993;Sim and Allen, 1998) and released ACh from their processes (Allen and Brown, 1996). Furthermore, neurons isolated in the same manner, grown on the same substrate, and maintained in identical growth media as those used in the present experiments (albeit as mass cell cultures) expressed the cholinergic marker choline acetyltransferase as determined by singlecell PCR (Allen and Brown, 2004). In this respect, therefore, they belong to that class of BF neurons conventionally regarded as cholinergic.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Thus, in previous experiments using these neurons in long-term culture, they showed the same electrophysiological properties as those reported for identified cholinergic BF neurons in situ (Allen and Brown, 1993;Sim and Allen, 1998) and released ACh from their processes (Allen and Brown, 1996). Furthermore, neurons isolated in the same manner, grown on the same substrate, and maintained in identical growth media as those used in the present experiments (albeit as mass cell cultures) expressed the cholinergic marker choline acetyltransferase as determined by singlecell PCR (Allen and Brown, 2004). In this respect, therefore, they belong to that class of BF neurons conventionally regarded as cholinergic.…”
Section: Discussionsupporting
confidence: 59%
“…A dissociated cell suspension of basal forebrain neurons was prepared as reported previously (Allen and Brown, 2004). Briefly, 12-to 14-d-old Sprague Dawley rat pups were anesthetized by chloroform inhalation before decapitation according to Home Office guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The sensitization produced by PGE 2 may be reversed by the capacity of K ATP to hyperpolarize the resting membrane potential and/or increase the rheobase of the action potential firing; these actions would decrease the excitability. Consistent with the reduction in excitability by K ATP channels, Allen and Brown (2004) reported that in magnocellular cholinergic neurons of the basal forebrain, activation of K ATP produced hyperpolarization of the membrane with a concomitant reduction in excitability. Their results also suggested that K ATP was tonically active at rest.…”
Section: Discussionmentioning
confidence: 55%
“…In this regard, K ATP channels control the release of insulin from pancreatic β cells (Ashcroft et al 1984;Ashcroft and Gribble 1998;Miki et al 1999;Schwanstecher et al 1998;Seino 1999) and blood flow in muscle, heart, and kidney tissue (Ashcroft 1988;Nelson and Quayle 1995;Terzic et al 1995;Yokoshiki et al 1998). In neurons, activation of K ATP results in membrane hyperpolarization that reduces excitability (Yamada et al 2001;Allen and Brown 2004) and activation of presynaptic K ATP channels can directly modulate neurotransmitter release from nerve terminals (Deist et al 1992;Ohno-Shosaku et al 1992;Watts et al 1995;Ye et al 1997). …”
Section: Introductionmentioning
confidence: 99%
“…However, the primary role of K ATP channels in many other central neurons is not glucosensing [84,90,99] . For instance, basal activity of K ATP channels can affect neuronal excitability in non-glucosensing neurons [100,101] . In the dentate granule neurons in the mouse hippocampus, K ATP channels are expressed with a high density [84,99] .…”
Section: Introductionmentioning
confidence: 99%